Innovations to identifying the effects of clear information visualization: reducing managers time in data interpretation. Issue 1 (2nd January 2018) - Garwood, Kathleen Campbell; Jones, Corey; Clements, Nicolle; Miori, Virginia
Abstract: Presentation of data analysis, especially for big data, must rely on graphics to clearly display patterns and provide evidence of relationships within the data. With clear, concise and communicative graphics, managers can gain insight or disseminate information quickly. This study uses a data visualization survey to ascertain how well participants answer simple questions when looking at two types of graphics: (a) crowded representation of data and (b) concise representation of data. Correct responses to questions posed for each type of visualization is the first outcome under investigation. The second outcome is the duration of time spent examining each visual before accurately answering the questions. Results show that participants are able to correctly answer more questions using clearer concise visuals in a shorter amount of time. Moreover, when managers are presented with clear and clean visual analysis, time can be saved and better decisions developed.